2010
DOI: 10.1074/jbc.m109.078881
|View full text |Cite
|
Sign up to set email alerts
|

Sp2 Is a Maternally Inherited Transcription Factor Required for Embryonic Development

Abstract: The Sp family of transcription factors is required for the expression of cell cycle-and developmentally regulated genes, and the deregulated expression of a handful of family members is associated with human tumorigenesis. Sp2 is a relatively poorly characterized member of the Sp family that, although widely expressed, exhibits little or no DNA binding or transcriptional activity in human and mouse cell lines. To begin to address the role(s) played by Sp2 in early metazoan development we have cloned and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…5B). It is worth noting that a virtually identical distribution of Sp2 expression has been detected in developing zebrafish embryos using a digoxigenin-labeled RNA probe derived from the zebrafish Sp2 3′ untranslated region [29]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5B). It is worth noting that a virtually identical distribution of Sp2 expression has been detected in developing zebrafish embryos using a digoxigenin-labeled RNA probe derived from the zebrafish Sp2 3′ untranslated region [29]. …”
Section: Resultsmentioning
confidence: 99%
“…In keeping with this supposition we have cloned the zebrafish Sp2 orthologue and shown that Sp2 is required for the completion of gastrulation [29]. Expression of full-length Sp2 message is particularly prominent in the embryonic forebrain of the mouse, suggesting that Sp2 may regulate region-specific genes within the developing central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Sp family members are coexpressed broadly, developmental defects exhibited by subtypespecific knockout mice indicate that their functions may only partially overlap (Supp et al, 1996;Marin et al, 1997;Bouwman et al, 2000;Nguyêñ-Trân et al, 2000;Göllner et al, 2001;van Loo et al, 2003). Recent studies indicate Sp2 is required for early embryonic development in mice and zebrafish (Baur et al, 2010;Xie et al, 2010), and Sp2 overexpression in skin stem cell and progenitor populations is oncogenic (Kim et al, 2010). Acute loss of Sp2 negatively regulates the proliferation of immortalized mouse fibroblasts (Baur et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Sp2 DNA-binding domain is the least conserved (75%) amongst Sp-family members and binds with high affinity (K d = 225 pM) to a consensus DNA-binding site (5'-GGGCGGGAC-3') that is distinct from that of Sp1 (810). Yet, in transient-transfection assays Sp2 only weakly trans -activates promoters carrying consensus Sp2-binding sites or well-characterized Sp-dependent promoters that are readily induced by Sp1 and Sp3 (8, 11). Despite its widespread expression, little or no soluble Sp2 DNA-binding activity has been detected in many human and mouse cell lines (8).…”
Section: Introductionmentioning
confidence: 99%